High prevalence of Gammapapillomaviruses (Gamma-PVs) in pre-malignant cutaneous lesions of immunocompetent individuals using a new broad-spectrum primer system, and identification of HPV210, a novel Gamma-PV type - Bolatti, Elisa Maria (2018)
Genus Gammapapillomavirus (Gamma-PV) is the most diverse and largest clade within the Papillomaviridae family. A novel set of degenerate primers targeting the E1 gene was designed and further used in combination with the well-known CUT PCR assay to assess HPV prevalence and genus distribution in a variety of cutaneous samples from 448 immunocompetent individuals. General HPV, Gamma-PV and mixed infections prevalence were significantly higher in actinic keratosis with respect to benign and malignant neoplasms, respectively (p = 0.0047, p = 0.0172, p = 0.00001). Gamma-PVs were significantly more common in actinic keratosis biopsies than Beta- and Alpha-PVs (p = 0.002). The full-length genome sequence of a novel putative Gamma-PV type was amplified by ‘hanging droplet’ long-range PCR and cloned. The novel virus, designated HPV210, clustered within species Gamma-12. This study provides an additional tool enabling detection of HPV infections in skin and adds new insights about possible early roles of Gamma-PVs in the development of cutaneous malignant lesions.